Effects of Soluble and Insoluble Non-Starch Polysaccharides on Growth Performance, Digestive Enzyme Activity, Antioxidant Capacity, and Intestinal Flora of Juvenile Genetic of Improvement of Farmed Tilapia (Oreochromis niloticus) - Liu, Yu; Deng, Junming; Tan, Beiping; Xie, Shiwei; Zhang, Wei (Frontiers in Marine Science, 2022)
This study aimed to evaluate the effects of soluble and insoluble non-starch polysaccharides (NSPs) on growth performance, digestive enzyme activity, antioxidant capacity, and intestinal flora of juvenile GIFT tilapia (Oreochromis niloticus). Four isonitrogenous and isolipidic experimental diets were formulated, including the FM diet (0% NSPs, FM), INSP diet (5.8% insoluble NSPs, INSP), SNSP diet (12.2% soluble NSPs, SNSP), and NSP diet (5.8% INSP and 12.2% SNSP, NSPs). Each diet was fed to triplicate groups of 40 fish (2.14 ± 0.04 g) per repetition for 10 weeks. Results showed that dietary supplementation with different types of NSPs significantly affected the digestive enzyme activity, antioxidant capacity, and intestinal flora of juvenile GIFT tilapia. Specifically, dietary supplementation with INSP significantly increased pepsin and intestinal lipase activity, while dietary supplementation with SNSP significantly decreased intestinal lipase activity and resulted in a significant decrease in plasma catalase, glutathione peroxidase, and total antioxidant capacity activity. Meanwhile, dietary supplementation with SNSP significantly increased the concentration of urea nitrogen and high-density lipoprotein cholesterol in plasma and alanine aminotransferase activity in plasma and hepatic. Moreover, LEfSe analysis showed that dietary supplementation with SNSP significantly increased the abundance of Bacteroidales, Bacteroidia, and Cellulosilyticum, while dietary supplementation with NSPs significantly decreased the abundance of Mycobacteriaceae, Mycobacterium_neoaurum, Corynebacteriales, and Mycobacterium. These results suggest that dietary INSP is an inert ingredient with limited effect, while dietary SNSP inhabited antioxidant capacity, induced liver damage, and altered the abundance of anaerobic/aerobic bacteria in the intestine of GIFT tilapia.